2016
DOI: 10.1136/jmedgenet-2015-103647
|View full text |Cite
|
Sign up to set email alerts
|

Mutations inLTBP3cause acromicric dysplasia and geleophysic dysplasia

Abstract: The constellation of features in these AD and GD cases, including postnatal growth retardation of long bones and lung involvement, is reminiscent of the null ltbp3 mice phenotype. We conclude that LTBP3 is a novel component of the microfibrillar network involved in the acromelic dysplasia spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
52
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 40 publications
2
52
0
2
Order By: Relevance
“…Geleophysic dysplasia (GPHYSD1, MIM231050; GPHYSD2, MIM614185; GPHYSD3, MIM617809) is a connective tissue disorder presenting with short stature, small hands and feet, cardiac valvular disease, hepatomegaly, joint contractures, and thickened skin (Rosser, Wilkinson, Hurst, McGaughran, & Donnai, ; Spranger, Gilbert, Tuffli, Rossiter, & Opitz, ; Vanace, Friedman, & Wagner, ). Although initially suspected to be a lysosomal storage disorder (Lipson, Kan, & Kozlowski, ; Wraith, Bankier, Chow, Danks, & Sardharwalla, ), GPHYSD was later recognized to be caused by mutations in genes encoding components of the extracellular matrix (ECM) including a disintegrin and metalloproteinase with thrombospondin motifs like 2 (ADAMTSL2, MIM612277) (GPHYSD1) (Le Goff et al, ), fibrillin 1 ( FBN1 , MIM134797) (GPHYSD2) (Le Goff et al, ), and latent transforming growth factor β (TGF‐β) binding protein 3 ( LTBP3 , MIM 602090) (GPHYSD3) (McInerney‐Leo et al, ). Transforming Growth Factor‐β (TGF‐β) is sequestered in an inactive and latent form by interactions with several ECM proteins and ordered polymers of fibrillin bind latent TGF‐β maintaining TFG‐β biologically inactive.…”
Section: Introductionmentioning
confidence: 99%
“…Geleophysic dysplasia (GPHYSD1, MIM231050; GPHYSD2, MIM614185; GPHYSD3, MIM617809) is a connective tissue disorder presenting with short stature, small hands and feet, cardiac valvular disease, hepatomegaly, joint contractures, and thickened skin (Rosser, Wilkinson, Hurst, McGaughran, & Donnai, ; Spranger, Gilbert, Tuffli, Rossiter, & Opitz, ; Vanace, Friedman, & Wagner, ). Although initially suspected to be a lysosomal storage disorder (Lipson, Kan, & Kozlowski, ; Wraith, Bankier, Chow, Danks, & Sardharwalla, ), GPHYSD was later recognized to be caused by mutations in genes encoding components of the extracellular matrix (ECM) including a disintegrin and metalloproteinase with thrombospondin motifs like 2 (ADAMTSL2, MIM612277) (GPHYSD1) (Le Goff et al, ), fibrillin 1 ( FBN1 , MIM134797) (GPHYSD2) (Le Goff et al, ), and latent transforming growth factor β (TGF‐β) binding protein 3 ( LTBP3 , MIM 602090) (GPHYSD3) (McInerney‐Leo et al, ). Transforming Growth Factor‐β (TGF‐β) is sequestered in an inactive and latent form by interactions with several ECM proteins and ordered polymers of fibrillin bind latent TGF‐β maintaining TFG‐β biologically inactive.…”
Section: Introductionmentioning
confidence: 99%
“…LTBP3 homozygous loss-of-function variants have been reported to cause dental abnormalities and short stature (DASS) in affected individuals between the ages of 2 and 28 years, but thoracic aortic disease has not been reported. [15][16][17][18] The proband of family TAA909 has DASS and also had multiple aortic and arterial aneurysms, including abdominal aortic aneurysm requiring surgical repair at the age of 44, aortic root dilation, and multiple visceral and peripheral arterial aneurysms at the age of 54 years (Table 1). His sisters inherited both LTBP3 variants and have DASS.…”
mentioning
confidence: 99%
“…Other eye findings reported in AD and GD include glaucoma (Saricaoglu et al, 2013;Zhang et al, 2004) and Brown syndrome (Faivre et al, 2001;McInerney-Leo et al, 2016). Zhang et al (2004) and Saricaoglu et al (2013) also observed an increased thickness of the cornea and lens.…”
mentioning
confidence: 91%